The roles of servicescape in the retail business - Luhita, Tiladela (Faculty of Economics and Business, Jenderal Soedirman University, 2018)
Retail business is a type of business which is directly in contact with consumers. Currently, the retail industry in Indonesia is significantly declining, with retail companies are closing down in 2017 as a result of the retail industry's downfall. Referring to the decline of business retail, it Rita Supermall, the first mall in Purwokerto, have to pay attention to some things in order not to face the same thing as other retail stores. One way to retain customers is by providing an excellent service environment through servicescape to achieve customer satisfaction. This research conducted in Banyumas Regency, with limited area selection that is around Purwokerto. The sample in this research is determined by non-probability sampling technique as much as 100 respondents that are by purposive sampling method, and multiple regression is employed to analyze the data. The results show that all of the hypotheses are accepted, it means all of the dimensions of the servicescape positively influence customer satisfaction.